Influence of Burst Repetitive Transcranial Magnetic Stimulation on chronic tinnitus - Bijan Forogh; Gholam Reza Raissi; Tannaz Ahadi; Mohammad Fereshtehnejad; Maryam Yazdi-Bahri (Afarand Scholarly Publishing Institute, 2013)
Background: Tinnitus is the perception of sound in the absence of an auditory stimulus and it is a common symptom in hearing system disorders. Chronic form affecting 5 to 15% of general population and in 1 to 3% of the population, it cause severe impairment of quality of life. Repetitive Transcranial Magnetic Stimulation (rTMS) effects on tinnitus have been evaluated in recent decades and has been shown that rTMS treatments may improve tinnitus symptoms. In this study the effects of Burst rTMS on patients with chronic tinnitus have been investigated. Methods: The study was a clinical trial. 28 patients, including 4 women (14.3%) and 24 men (85.7%) were treated with Burst rTMS in 4 sessions and severity of tinnitus was evaluated with visual analog scale before, after and on month after treatment. Results: the severity of tinnitus significantly reduced after treatment and one month later, with statistically significant difference (P value=0.001). Conclusion: According to the results of treatment including reducing the intensity of tinnitus with statistically significant difference and lasting effects even after one month of treatment, Burst rTMS can be considered as an effective treatment.